Prevalência de Oestrus ovis (Diptera: Oestridae) em ovinos da região Central de São Paulo, Brasil - da Silva, Bruna Fernanda [UNESP] (2012)
The heads of 139 slaughtered sheep were examined with the aim of determining Oestrus ovis prevalence and infestation intensity in the central region of the State of São Paulo, Brazil. Heads from slaughtered sheep were examined and the first (L1), second (L2) and third (L3) O. ovis larval instars were recovered from the nasal and sinus cavities. O. ovis larvae were detected in 13.7% of the sheep analyzed. The monthly mean intensity of infestation ranged from 1 to 10.2 larvae per infested head, with general mean intensity of 4.5 larvae/infested head. Of the total of 85 larvae, 21.2% were L1, 37.6% L2 and 41.2% L3. In conclusion, all different O. ovis larvae instars were recovered from slaughtered animals, which demonstrates the existence of favorable climatic conditions for the fly activity and larval development of O. ovis in sheep raised in the Central region of the State of São Paulo.